OILCA : enhancing the competitiveness and reducing the carbon footprint of the olive oil sector through waste management optimisation and the establishment of an ecological label - Carvalho, Joana (2012)
OiLCA is an international project by the INTERREG IVB SUDOE communitarian initiative. It aims to improve the competitiveness of the olive sector in the south-western Europe region, which includes Spain, Portugal and the South of France. The OiLCA methodology is based on life cycle assessment (LCA) and life cycle cost (LCC) to identify opportunities for the optimization of olive oil production. Olive oil production is an important ago-industrial sector in the Mediterranean region of Europe. SUDOE space produces approximately 47% of the world’s olive oil. Due to its organoleptic characteristics and health benefits, olive oil consumption has increased in European zone, by 50% during the last twenty years, reaching an estimated 1.85 million tons in 2009. The intrinsic quality of olive oil extracted corresponds to approximately 20% of the olive’s weight. The residues, called grounds, are a mixture of stones, pulp and residual oil. Approximately 7.25 million tons of residues are generated yearly in the SUDOE space. The management of these residues remains a challenge because of their predominance and unavoidable production. Therefore, opportunities for waste management must be identified and brought forward by taking into account the available or emergent technology, which may result in both economic and environmental benefits.